Ações para controle da tuberculose na população em situação de rua: fatores associados e desempenho de profissionais da Atenção Primária à Saúde - Rodrigo Pinheiro Fernandes de Queiroga (2018)
Tuberculosis (TB) represents a severe public health problem and is associated with poverty and social inequity. Among the vulnerable groups, we highlight the homeless persons, which, among other factors, faces difficulties in achieving care in the Brazilian Unified Health System, including in Primary Health Care (PHC). Accordingly, this study was aimed to analyze the development of actions to control TB in the homeless persons of the town of Campina Grande PB. This is an evaluative research with a cross-sectional and epidemiological design. The population was composed of 171 higher education professionals from the Family Health Strategy (FHS). We drew up a questionnaire based on the actions recommended and concepts adopted by the Brazilian Ministry of Health to control TB in homeless persons. We conducted the Principal Component Analysis (PCA) with a view to simplifying the data structure. The analysis of reliability of the factors found was held by Cronbachs alpha. We conducted the analysis of performance and reliability of the variables extracted from PCA, with the performance level classified as satisfactory, partially satisfactory, incipient or unsatisfactory. Subsequently, we performed multiple linear regression analysis with the purpose of finding variables related to TB care in homeless persons. PCA enabled the identification of a pattern of relationship among the variables that resulted in a model with two correlated factors. In the actions to control TB in homeless persons (Factor 1), the variables were classified as incipient and partially satisfactory. In the support that teams should receive to drive actions to control TB in homeless persons (Factor 2), the variables were classified as unsatisfactory and incipient. We noted that 22% of the FHS professionals in Campina Grande do not have appropriate knowledge of homeless persons in their respective areas of operation. Moreover, for 35% of the interviewed, the care of TB cases is centralized in some professional categories. Among the factors associated with the development of the actions recommended by the Ministry of Health to control TB in homeless persons, we should highlight the nursing professionals with experience in the care of homeless persons, who attended training on TB in homeless persons, with access to care manuals for homeless persons and who had the support from the Street Medical Office Team (ECR, as per its Portuguese acronym). The model can explain 26.9% of the data variability. We noted that the particularities of homeless persons are not considered to the development of actions to control TB in this public, when these are offered, running against the recommendations of the Ministry of Health. The offer or accomplishment of actions to control TB is similarly conducted for the general population and is often restricted to the referral of patients to the reference unit. We hope that the results obtained in this study may contribute to the organization of PHC in Campina Grande by subsidizing the operationalization of more appropriate responses regarding the TB control in homeless persons in accordance with the recommendations of the Ministry of Health.